2006
DOI: 10.1002/jnr.21012
|View full text |Cite
|
Sign up to set email alerts
|

De Novo synthesis of CREB in a presynaptic neuron is required for synaptic enhancement involved in memory consolidation

Abstract: Interaction between the activator type of cyclic AMP response element binding protein (CREB1) and the repressor type (CREB2) results in determining the emergence of long-lasting synaptic enhancement involved in memory consolidation. However, we still do not know whether the constitutively expressed forms of CREB are enough or the newly synthesized forms are required for the synaptic enhancement. In addition, if the newly synthesized forms are needed, we must determine the time for translation of CREB from its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…It has been hypothesized that the cerebral giant cells and the B2 motor neurons play key roles in mediating the learning and LTM formation of this CTA (Kojima et al, 1997;Kojima et al, 2000;Kojima et al, 2001;Hatakeyama et al, 2004a;Sadamoto et al, 2004b). Consistent with this hypothesis are the data showing that altered gene activity and new protein synthesis must occur in these and other neurons if LTM is to form following the CTA procedure Hatakeyama et al, 2004b;Hatakeyama et al, 2006;Azami et al, 2006;Wagatsuma et al, 2006). In addition, our recent findings showed that snails are both able to discriminate different tastes and continue to eat other foods following the CTA procedure (Sugai et al, 2006).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…It has been hypothesized that the cerebral giant cells and the B2 motor neurons play key roles in mediating the learning and LTM formation of this CTA (Kojima et al, 1997;Kojima et al, 2000;Kojima et al, 2001;Hatakeyama et al, 2004a;Sadamoto et al, 2004b). Consistent with this hypothesis are the data showing that altered gene activity and new protein synthesis must occur in these and other neurons if LTM is to form following the CTA procedure Hatakeyama et al, 2004b;Hatakeyama et al, 2006;Azami et al, 2006;Wagatsuma et al, 2006). In addition, our recent findings showed that snails are both able to discriminate different tastes and continue to eat other foods following the CTA procedure (Sugai et al, 2006).…”
Section: Introductionmentioning
confidence: 74%
“…the consolidation process) following learning requires both altered gene activity and de novo protein synthesis (Davis and Squire, 1984;Milner et al, 1998;Kandel and Squire, 1999;McGaugh and Izquierdo, 2000;Kandel, 2001;Sangha et al, 2003a;Epstein et al, 2003;Epstein et al, 2004;Ribeiro et al, 2005;Azami et al, 2006;Wagatsuma et al, 2006). An advantage of using a one-trial conditioning procedure that results in LTM formation is that the consolidation process must begin at some time following the single pairing of the stimuli; providing a precise point in time to apply amnesiac agents.…”
Section: Extinction Of the Conditioned Taste Aversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of preand postsynaptic compartments is important for examining signaling and protein synthesis, which occurs in both compartments. [7][8][9][10][11][12][13] The Percoll-sucrose gradient is a crude purification so we saw minor cellular, nuclear and organelle contamination in the SN fraction but the overall separation was good.…”
Section: Preparation Of Homogenate and Sns 1-4 4 Representative Resumentioning
confidence: 99%